Metabolic syndrome is associated with prostate enlargement: a systematic review, meta-analysis, and meta-regression on patients with lower urinary tract symptom factors. (December 2021) - Omran, Asma; Leca, Bianca M.; Oštarijaš, Eduard; Graham, Natasha; Da Silva, Ana Sofia; Zaïr, Zoulikha M.; Miras, Alexander D.; le Roux, Carel W.; Vincent, Royce P.; Cardozo, Linda; Dimitriadis, Georgios K.
Background: Metabolic syndrome (MetS) is defined by at least three of the following five criteria: blood pressure ⩾130/85 mmHg, fasting blood glucose ⩾5.6 mmol/l, triglycerides concentration ⩾1.7 mmol/l, waist circumference ⩾102 cm (for men), and high-density lipoprotein cholesterol concentration <1.03 mmol/l (for men). MetS has been associated with worse lower urinary tract symptoms (LUTS) and higher International Prostate Symptom questionnaire scores. Materials and Methods: MEDLINE, Cochrane, ClinicalTrials.gov, and SCOPUS were critically appraised for all peer-reviewed manuscripts that suitably fulfilled our protocol's inclusion criteria established a priori . Meta-analytical and meta-regression calculations were performed in R using the Sidik–Jonkman and Hartung–Knapp random effects model and predefined covariates. Results: A total of 70 studies ( n  = 90, 206) were included in qualitative synthesis. From these, 60 studies focused on MetS and LUTS: 44 reported positive correlations, 5 reported negative correlations, 11 reported no association, and 10 studies focused on MetS and total prostate volume (TPV). MetS positively correlated with moderate LUTS [odds ratio (OR)  = 1.56, 95% confidence interval (CI) = 1.35–1.80], severe LUTS (OR = 2.35, 95% CI = 1.82–3.03), overactive bladder (OAB; OR = 3.2, 95% CI = 1.6–5.8), and nocturia severity (OR = 2.509, 95% CI = 1.571–4.007) at multivariate analysis. A total of 30 studies ( n  = 22, 206) were included in meta-analysis; MetS was significantly associated with higher TPV (mean differences = 4.4450 ml, 95% CI = 2.0177–6.8723), but no significant predictive factors for effect sizes were discovered. Conclusion: Our meta-analysis demonstrates a significant association between the aggravating effects of MetS, which commonly coexists with obesity and benign prostate enlargement.